Teaching Residents Genomic Pathology: A Novel Approach for New Technology - Haspel, Richard L. (2013)
Genomics-based diagnostics have become part of patient care. As pathologists have the expertise in clinical laboratory testing as well as access to patient samples, all genomic medicine is genomic pathology. This article will review the evidence that there is a critical need for pathology resident training in genomics. Several individual program curricula are described as well as the progress of the Training Residents in Genomic (TRIG) Working Group. This group has made significant advances towards developing, implementing and evaluating a national curriculum in genomics for pathology residents. The novel approach of the TRIG Working Group can be used as a model for training pathology professionals in any new technology.